Transition of metallic and insulating Ti sub-oxides in bipolar resistive switching TiOx/TiOy frameworks due to oxygen vacancy drifts - Bae, Yoon Cheol; Lee, Ah Rahm; Kwak, June Sik; Im, Hyunsik; Do, Young Ho; Hong, Jin Pyo (SPRINGER, 2011)
Bilayer TiO (x) (oxygen rich, region 1)/TiO (y) (oxygen poor, region 2) homojunctions were evaluated as resistive switching elements where the TiO (x) layers were designed with various oxygen contents. Depending on the oxygen ion content, controllable memory windows were observed by changing the off-state (high-resistance state), while the on-state (low resistance) was left with very little change. The cause of the variable memory windows in resistive switching phenomena appears to be the increasing amounts of movable oxygen ions between the TiO (x) and TiO (y) layers. In addition, the X-ray photoelectron spectroscopy measurements of the initial, low resistance, and high-resistance states in the homojunctions demonstrated the possible change of metallic and insulating Ti sub-oxide phases at the interfaces and oxygen ion rich region due to the migration of oxygen ions.